Design and analysis of vortex generator for a HEV model - Johari, Ismail (2008)
Design and analysis of vortex generator by using Computational Fluid Dynamic (CFD) on Hybrid Electrical Vehicle (HEV) model was carried out on this project. One of the main causes of aerodynamic drag for vehicle is the separation of flow near the vehicle’s rear end. To control the flow separation, delta wing shaped vortex generator is test for application to the roof end of vehicle. A vortex generator (VG) is an aerodynamic surface, consisting of a small vane that creates a vortex. The model of vehicle that can be used to conduct this project is HEV model for Proton Iswara. The objective of the project is to determine the percentage of drag reductionby using VG, ranging from 60 km/h to 120 km/h that designed by Computational Aided Design (CAD) in SolidWorks software. Vortex generator themselves create drag, but they also reduce drag by preventing flow separation at downstream. The overall effect of vortex generators can be calculated by totaling the positive and negative effects. Drag coefficient can be obtained by using output of CFD then export into FEM analysis to find the value of drag force to be applied into aerodynamic drag coefficient equation. Besides that, CFD simulation results such as contour plot also used to analyze the characteristic of streamline flow at the rear end of HEV model. Comparison of drag coefficient between the model of HEV vehicle with and without vortex generator must be done to achieve the project objectives. The application of VG had shown that 6.61 percent reduction in aerodynamic drag coefficient.